Golgi-Cox Staining Step by Step - Zaqout, Sami; Kaindl, Angela M. (Frontiers in Neuroanatomy, 2016)
Golgi staining remains a key method to study neuronal morphology in vivo. Since most protocols delineating modifications of the original staining method lack details on critical steps, establishing this method in a laboratory can be time-consuming and frustrating. Here, we describe the Golgi-Cox staining in such detail that should turn the staining into an easily feasible method for all scientists working in the neuroscience field.